The effect of microstructural changes on the rupture behavior of gas turbine damping bolt superalloy (Nimonic 90) after long service time. (March 2023) - Shajari, Yazdan; Beigi, Majid; Porhonar, Mohammad
Highlights: In this paper, microstructural alterations in gas turbine damping bolts of ALSTOM 11N2 made of Nimonic 90 at a service temperature of approximately 570 to 620 °C are reviewed and discussed. During service, based on the diffusion of Cr from the grain to the grain boundary, the grain boundaries thicken, and the stabilized M23C6 carbides fuse with the Cr to form a carbide film. With the depletion of Cr from the grains in damping bolts, which served for 100, 000 h, refractory elements formed harmful TCP phases. The service exposed sample's rapture resistance was much less than that of the new sample. The failure mechanism of both samples was a brittle intergranular failure. Continuous loading led to cracks in TCP phases due to high brittleness. Besides, these cracks propagated into the matrix either through the grain boundaries or inside the grain. The path of crack propagation strongly depended on the location of the TCP phase and other boundary and grain boundaries transformation. Abstract: The present study investigated the microstructure of superalloy gas turbine damping bolt. These damping bolts were selected from new and service-exposed ones made of nickel-based Nimonic 90, which had been served for a long time. The microstructure of new sample had an austenitic matrix with many twins. These twins were located in the intergranular and intragranular regions of the primary carbides. Fine gamma-prime precipitates also could be found in the field. However, due to the high amount of service time, the arranged structure turned into a complex one in which the Sigma and Mayo phases with the Widmanstätten pattern appeared near the grain boundaries. Therefore, secondary continuous carbides formed near the grain boundary, and γ′ precipitates grew, which increased the hardness of the samples by about 30 Vickers. The mentioned microstructural changes reduced the creep rupture to 140 MPa at 870 °C in 11 h, while the sample had a creep life of about 21 h. This indicates that the resulting microstructural changes reduced brittleness and creep life. The soft intergranular failure mechanism in the new damping bolt became an intergranular mechanism. Moreover, the effects of intragranular failure were also abundant.